Telesna vadba pri srčno-žilnih bolnikih - Kambič, Tim (Šport (Ljubljana), 2019)
Cardiovascular diseases represent a leading cause of morbidity and mortality worldwide, wherein cardiovascular disease prevention plays a crucial role. Secondary prevention and medical therapy of coronary artery disease and/or heart failure take place within cardiac rehabilitation programs, with exercise training representing a key component. The preferred exercise training is still aerobic training, while resistance training recently gain its popularity. The aim of this article is to review the various systemic and peripheral effects of exercise on health related outcomes in cardiovascular disease patients. Furthermore, the article presents the current exercise prescription guidelines, with exact description of different exercise modalities according to each phase of cardiac rehabilitation. Lastly, future directions for applied research and clinical practice are also discussed.
Keywords: aerobic exercise; aerobna vadba; cardiovascular diseases; secondary prevention; sekundarna preventiva; sport; srčno-žilne bolezni; strength exercise; šport; vadba za moč